A Graduate Student’s Thesis Writing Process - Geby Maryono; Emi Emilia; Gin Gin Gustine (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
A thesis is a challenging scholarly writing task at the university level. Previous studies showed that an effective writing process is necessary to complete writing tasks. Therefore, it is assumed that effective process is also necessary to complete thesis writing well. This qualitative research applied a case study design to explore the writing process of a proficient graduate student in writing a thesis. The participant of this study was a graduate student from a private university with cum laude predicate. The interview was used as the main data source with document analysis as a data source for triangulation. Models of writing processes from the process-genre approach were used as the main theory to discuss the findings. This research revealed that the student went through stages of writing well with various activities. In the pre-writing stage, the student reflected on her surrounding to find the problem to solve, read numerous references and discussed the topic with the experts to gain a deeper understanding. In the drafting stage, the student always provided a specific time for writing and simultaneously integrated her reading into her writing. In the revision stage, the student got feedback from many experts, then she selected the feedback before applying them to her writing. During the revision, the student also simultaneously edited her writing. She also published her thesis several times. The student gained many benefits from each stage of writing, such as improving academic writing skills and changing mindset in perceiving writing specifically and perceiving life in general. However, she also faced challenges during the writing process, such as feeling bored with the tedious process and dealing with her perfectionist to stay realistic. From this research, it can be seen that proficient students recursively went through each stage of the writing process, which resulted in a quality thesis.